2016
DOI: 10.1007/s12011-016-0915-9
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Administration Alleviates Toxicity of Chromium(VI) in the Chicken Brain

Abstract: Selenium (Se) can play a protective role against heavy metal toxicity. This experiment aims to evaluate the effect of Se supplementation at different doses on the chicken brains. Oxidative stress was induced in the chicken brains by chromium(VI). A total of 105 Hyland brown male chickens were randomly divided into seven groups, including the control group, poisoned group [6%LD KCrO body weight (B.W.)], and detoxification groups KCrO (6%LD) + Se (0.31, 0.63, 1.25, 2.50, and 5.00 NaSeO mg/kg B.W.) orally in wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…In addition, Se combination with heavy metals, such as Cd, Hg, and Pb, reduces the toxicity of these elements in different animals and organs . Studies have shown that Se could reduce the toxicity of Cr(VI) in chicken brain, but the interactions in chicken liver remain unknown, the present study investigated whether the optimal dose of Se can inhibit the liver damage caused by Cr(VI) and discussed the hepatic oxidative damage induced by Cr(VI) in chicken liver. Our study increased dose groups of Se, so the limits of the combined effect of Se–Cr(VI) would be measured more accurately.…”
Section: Introductionmentioning
confidence: 85%
“…In addition, Se combination with heavy metals, such as Cd, Hg, and Pb, reduces the toxicity of these elements in different animals and organs . Studies have shown that Se could reduce the toxicity of Cr(VI) in chicken brain, but the interactions in chicken liver remain unknown, the present study investigated whether the optimal dose of Se can inhibit the liver damage caused by Cr(VI) and discussed the hepatic oxidative damage induced by Cr(VI) in chicken liver. Our study increased dose groups of Se, so the limits of the combined effect of Se–Cr(VI) would be measured more accurately.…”
Section: Introductionmentioning
confidence: 85%
“…In another study, Se protected from chromium (CrVI)-induced damage in chicken brain. The supplementation of Se to these chickens prevented negative changes in the levels of reduced glutathione (GSH), mitochondrial membrane potential, and Ca 2+ -ATPase activity induced by Cr in brain tissue [42]. Protective effects of Se were also described against lithium-provoked oxidative stress in FaDu and Vero cell lines [43].…”
Section: Selenium and Its Health Effects In Humans And Animalsmentioning
confidence: 99%
“…A protective effect of selenium was also reported against toxicity of other heavy metals, such as chromium (against chromium-induced oxidative and cellular damage in thyroid gland [ 162 ], chromium toxicity in the brain [ 163 ] and chromium-induced nephrotoxicity [ 164 ]), cadmium (the protection of jejunal epithelial cells from cadmium-induced DNA damage [ 165 ], an antagonistic effect of selenium on cadmium-induced damage of kidney [ 166 ], ameliorative effect against cadmium chloride-induced neuro- and nephrotoxicity [ 167 ]), and lead (against lead toxicity on the antioxidant system [ 168 ]), or also overabundance of iron. Selenium reduces the adverse impacts of excess iron intake.…”
Section: Biochemistry Of Seleniummentioning
confidence: 99%